Clinical Characteristics and Outcomes in Asian Patients With Premature Coronary Artery Disease: Insight From the FOCUS Registry. (July 2019) - Qu, Ya'nan; Zhang, Feng; Yang, Ji'e; Dai, Yuxiang; Li, Chenguang; Yang, Hongbo; Gao, Yang; Yao, Kang; Huang, Dong; Lu, Hao; Ma, Jianying; Qian, Juying; et al.
Objectives: Premature coronary artery disease (PCAD) is increasingly common in Asian countries; however, less is known regarding its characteristics and clinical outcomes. This study aims to describe clinical characteristics and investigate clinical outcomes in real-world Asian patients with PCAD. Methods: A total of 4700 Asian patients undergoing drug-eluting stent implantation were included in our study and divided into PCAD group and mature CAD (MCAD) group according to their onset age. All patients were followed up for 3 years to observe their clinical outcomes. Results: Patients with PCAD were more likely to be associated with acute coronary syndrome (ACS; P = .03) and acute occlusive lesion ( P < .001). Reference diameter ( P < .001) and lesion diameter stenosis ( P = .001) were significantly greater in PCAD group. Conversely, the MCAD group was more likely to be associated with left main disease, severe calcification lesion and small vessel involvement. The cumulative incidences of major adverse cardiovascular event (MACE; P = .007), cardiovascular death ( P < .001), and all cause death ( P < .001) were significantly lower in PCAD group than those in MCAD group. Conclusions: Although more often manifested as ACS, PCAD is associated with lower risks of MACE and cardiovascular death than MCAD in real-world Asian population.